An Examination of the Robustness of the Weekend Effect - Connolly, Robert A. (Journal of Financial and Quantitative Analysis, 1989)
This paper analyzes the robustness of the day-of-the-week (DOW) and weekend effects to alternative estimation and testing procedures. The results show that sample size can distort the interpretation of classical test statistics unless the significance level is adjusted downward. Specification tests reveal widespread departures from OLS assumptions. Hypothesis tests results are reported using robust econometric methods and a GARCH model. The strength of the DOW and weekend effect evidence appears to depend on the estimation and testing method. Both effects seem to have disappeared by 1975.